Role of Nurses: Dietary Promotion Based on The Dietary Approaches to Stop Hypertension in Person with Hypertension - Leesagul, Preeya; Juntarawijit, Yuwayong (NU Journal of Nursing and Health Sciences, 2025)
Hypertension is a major global health problem and a leading cause of premature death worldwide. Lifestyle modification is one of the standard treatments for managing hypertension. The Dietary Approaches to Stop Hypertension (DASH) diet has been proven effective in reducing blood pressure in hypertensive patients. The DASH diet emphasizes reducing sodium intake while increasing the consumption of foods rich in potassium, magnesium, calcium, and healthy sources of protein, such as vegetables, fruits, whole grains, low-fat dairy products, and legumes. Additionally, the DASH diet promotes the reduction of saturated fats, trans fats, and added sugars, helping to balance nutrients that benefit cardiovascular health. Essential minerals like potassium help expel excess sodium from the body, while magnesium and calcium play roles in regulating the contraction and relaxation of blood vessels. These outcomes contribute to lowering blood pressure and reducing the long-term risk of cardiovascular diseases. The promotion of this dietary approach is a crucial role for nurses in educating, counseling, monitoring, and evaluating person with hypertension. Nurses also play a key role in motivating patients, supporting their families and caregivers, and collaborating with interdisciplinary teams to ensure that hypertensive individuals can sustainably modify their dietary behaviors.